Análisis del impacto de una guía de prevención del ciberacoso sobre la asertividad. Un estudio de caso con estudiantes de grado 7º de una institución educativa de Soacha - Carrillo Bombiela, Ferney (Universidad Antonio Nariño, 2024)
The socioemotional competencies are crucial in education to promote peaceful coexistence. Assertiveness, in particular, enables students to express emotions and resolve conflicts, both in the classroom and online. With the increase in global school violence,